Residents' attitudes towards different tourist offers: Maldonado-Punta del Este conurbation (Uruguay) - JoseŔamoń Cardona; Daniel Aĺvarez Bassi; Mariá Dolores Sańchez-Fernańdez (European Journal of Government and Economics (EJGE), 2019)
The study of residents' attitudes is fundamental for tourist destinations managers. Residents form their attitude towards tourism through a cost-benefit analysis based on their perception of tourism impacts. The objective of this paper is to analyse the relationship between the perception of the different types of impacts, the general attitude toward tourism and various types of tourism offer: sport tourism, maritime tourism, nature tourism and sun and beach tourism. The analysis of the data was performed using Partial Least Squares on a sample of 420 residents of the Maldonado-Punta del Este conurbation, interviewed in 2016. The strongest causal relationship is between general attitude and acceptance of sun and beach tourism, the traditional offer in the region. The main conclusion is that a more favourable attitude to tourism does not imply greater support for any type of tourism. It is not possible to generalize the support to tourism to any tourism project, and tourist destinations managers must take it into account.
Keywords: C88; L83; Z32; 330; tourist offer; attitudes; Punta del Este; Uruguay